TINGKAT KEPUASAN ANGGOTA DAN FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PARTISIPASI ANGGOTA KUD MINA JAYA KECAMATAN BUMI WARAS DI KOTA BANDAR LAMPUNG - Rahmawati Handayani; Dyah Aring Hepiana Lestari; Ktut Murniati (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This research aims to analyze the level of satisfaction members, and the factors that affect on the level of participation members of KUD Mina Jaya in Bumi Waras subsdistrict of Bandar Lampung City. This research is condutedby survey method. Respondents of this research consist of fishermen (ship owner, sailor, ship crew, and ship machine) and nonfisherman (fish merchant). The research respondents constitutes of 87 people, consist of 68 fishermen and 19 nonfisherman and the research data is colledcted inJanuary to May 2017. The results of this research showed that the satisfaction felt by members of the inner ministry RAT, mandatory savings, and utilization of business unit services in categories “satisfied”. Based on the results of IPA, the main priority attributes were sufficient physical infrastructure, staff support, and availability of information boards. The age, length of membership, gender, jobs, and member’s satisfaction of cooperation services were positively correlated to the level of member participation of RAT attending. The length of membership was positively correlatedto the level of member participation in purchasing obligatory deposits. Family burden, jobs, and member’s satisfaction of cooperation services alsopositively correlatedto the level of member’s participation on untilised the business unit services.Key words: cooperative, participation, satisfaction